(untitled) (World Bulletin of Management and Law, 2024)
“An amicus curiae is someone who usually wishes to influence the outcome of a trial,” as noted in the legal literature1 . The term amicus curiae can have different meanings. Traditionally, the most common form of amicus curiae is an unrepresented party, or person appearing to represent an interest, at the request of the court.